Increased cortical thickness in nodes of the cognitive control and default mode networks in psychosis of epilepsy. (October 2022) - Allebone, James; Wilson, Sarah J; Bradlow, Richard C J; Maller, Jerome; O'Brien, Terry; Mullen, Saul A; Cook, Mark; Adams, Sophia J; Vogrin, Simon; Vaughan, David N; Connelly, Alan; Kwan, Patrick; et al.
..Highlights: · POE is characterised by cortical thickening relative to EC. · Thickening occurs primarily in nodes of the CCN and DMN. · Interictal psychosis is characterised by cortical thickening in left occipital and temporal regions relative to EC. · This was also evident to a lesser extent in postictal psychosis. · A novel mechanism for cortical thickening in POE is proposed whereby normal synaptic pruning processes are interrupted by seizure onset. Abstract: Objective: To explore the cortical morphological associations of the psychoses of epilepsy. Methods: Psychosis of epilepsy (POE) has two main subtypes - postictal psychosis and interictal psychosis. We used automated surface-based analysis of magnetic resonance images to compare cortical thickness, area, and volume across the whole brain between: (i) all patients with POE ( n = 23) relative to epilepsy-without psychosis controls (EC; n = 23), (ii) patients with interictal psychosis ( n = 10) or postictal psychosis ( n = 13) relative to EC, and (iii) patients with postictal psychosis ( n = 13) relative to patients with interictal psychosis ( n = 10). Results: POE is characterised by cortical thickening relative to EC, occurring primarily in nodes of the cognitive control network; (rostral anterior cingulate, caudal anterior cingulate, middle frontal gyrus), and the default mode network (posterior cingulate, medial paracentral gyrus, and precuneus). Patients with interictal psychosis displayed cortical thickening in the left hemisphere in occipital and temporal regions relative to EC (lateral occipital cortex, lingual, fusiform, and inferior temporal gyri), which was evident to a lesser extent in postictal psychosis patients. There were no significant differences in cortical thickness, area, or volume between the postictal psychosis and EC groups, or between the postictal psychosis and interictal psychosis groups. However, prior to correction for multiple comparisons, both the interictal psychosis and postictal psychosis groups displayed cortical thickening relative to EC in highly similar regions to those identified in the POE group overall. Significance: The results show cortical thickening in POE overall, primarily in nodes of the cognitive control and default mode networks, compared to patients with epilepsy without psychosis. Additional thickening in temporal and occipital neocortex implicated in the dorsal and ventral visual pathways may differentiate interictal psychosis from postictal psychosis. A novel mechanism for cortical thickening in POE is proposed whereby normal synaptic pruning processes are interrupted by seizure onset.